Improving Students’ Writing Skill by Using Role, Audience, Format, Topic (R.A.F.T) Strategy - Intan, Angel Sophia (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
The writing skills of students in class VIII A of SMP N 2 Jujuhan Bungo are still low. Evaluation of student assessment is categorized as low because of a number of aspects, namely students have difficulty understanding ideas in writing, preparation in understanding ideas in writing, inadequate vocabulary, inadequate use of learning methods applied by teachers in class. For this reason, this research was conducted in developing student competencies in writing by applying the RAFT method. This study used class action research (PTK) with the subject of the study as many as 25 students of class VII A of SMPN 2 Jujuhan Bungo. The study went through two cycles that were divided into five meetings. This research was supported by informants collected in the form of writing assignments, writing tests, interviews, and field recordings. The results of the study based on field notes of cycle I and cycle II showed that the average value of students' writing ability increased from cycle I to 66.08 increased to 74.24 in cycle II. This research resulted in the improvement of students' writing skills through the RAFT method which was influenced by several aspects, namely material, media, learning activities, classroom management, teacher approaches and teacher strategies.